The female upper reproductive tract harbors endogenous microbial profiles - Canha-Gouveia, Analuce; Pérez-Prieto, Inmaculada; Rodríguez, Carmen Martínez; Escamez, Teresa; Leonés-Baños, Irene; Salas-Espejo, Eduardo; Prieto-Sánchez, Maria Teresa; Sánchez-Ferrer, Maria Luisa; Coy, Pilar; Altmäe, Signe (Frontiers in Endocrinology, 2023)
The female reproductive tract harbours unique microbial communities (known as microbiota) which have been associated with reproductive functions in health and disease. While endometrial microbiome studies have shown that the uterus possesses higher bacterial diversity and richness compared to the vagina, the knowledge regarding the composition of the Fallopian tubes (FT) is lacking, especially in fertile women without any underlying conditions. To address this gap, our study included 19 patients who underwent abdominal hysterectomy for benign uterine pathology, and 5 women who underwent tubal ligation as a permanent contraceptive method at Hospital Clínico Universitario Virgen de la Arrixaca de Murcia (HCUVA). We analyzed the microbiome of samples collected from the FT and endometrium using 16S rRNA gene sequencing. Our findings revealed distinct microbiome profiles in the endometrial and FT samples, indicating that the upper reproductive tract harbors an endogenous microbiome. However, these two sites also shared some similarities, with69% of the detected taxa Being common to both. Interestingly, we identified seventeen bacterial taxa exclusively present in the FT samples, including the genera Enhydrobacter, Granulicatella, Haemophilus, Rhizobium, Alistipes, and Paracoccus, among others. On the other hand, 10 bacterial taxa were only found in the endometrium, including the genera Klebsiella, Olsenella, Oscillibacter and Veillonella (FDR <0.05). Furthermore, our study highlighted the influence of the endometrial collection method on the findings. Samples obtained transcervically showed a dominance of the genus Lactobacillus, which may indicate potential vaginal contamination. In contrast, uterine samples obtained through hysterescopy revealed higher abundance of the genera Acinetobacter, Arthrobacter, Coprococcus, Methylobacterium, Prevotella, Roseburia, Staphylococcus, and Streptococcus. Although the upper reproductive tract appears to have a low microbial biomass, our results suggest that the endometrial and FT microbiome is unique to each individual. In fact, samples obtained from the same individual showed more microbial similarity between the endometrium and FT compared to samples from different women. Understanding the composition of the female upper reproductive microbiome provides valuable insights into the natural microenvironment where processes such as oocyte fertilization, embryo development and implantation occur. This knowledge can improve in vitro fertilization and embryo culture conditions for the treatment of infertility.